2020
DOI: 10.3332/ecancer.2020.1082
|View full text |Cite
|
Sign up to set email alerts
|

Association of viral load and physical status of HPV-16 with survival of patients with head and neck cancer

Abstract: Introduction: Head and neck cancers (NHCs) are of multifaceted origins, and tobacco and alcohol are the primary risk factors. Currently, other factors associated with the genesis of these tumours are being considered, among these viral infections, especially human papillomavirus (HPV) infection. Objective: The objective was to evaluate HPV infection, HPV-16 E6 load and its physical status in patients with squamous cell carcinoma in the head and neck and evaluate its effects in the survival of these patients. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
2
8
0
1
Order By: Relevance
“…HPV 44 belongs to a mucosotropic group of HPVs found in benign and malignant lesions of the anogenital tract and fortuitously in tissues and lesions of the oral cavity, oropharynx, and esophagus [ 27 ]. A number of samples in our study contained more than one HPV type, which is in line with some [ 32 , 35 , 42 , 43 , 44 , 57 , 65 ] but not all studies [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…HPV 44 belongs to a mucosotropic group of HPVs found in benign and malignant lesions of the anogenital tract and fortuitously in tissues and lesions of the oral cavity, oropharynx, and esophagus [ 27 ]. A number of samples in our study contained more than one HPV type, which is in line with some [ 32 , 35 , 42 , 43 , 44 , 57 , 65 ] but not all studies [ 33 ].…”
Section: Discussionsupporting
confidence: 88%
“…Some researchers have used tests to detect all known high-risk and low-risk genotypes. However, HPV 43/44 was not observed [ 37 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. There are no guidelines for HPV testing as regards head and neck cancer, and the methods to detect HPV DNA in oral samples have not been standardized yet [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 28 HPV16 positive samples, 86% displayed integration, possessed low viral load and correlated to poor prognosis. [100]. Supporting these results, Koneva et al showed that patients with (RNAseq determined) integration-positive oropharyngeal and oral cavity tumors had statistically significant worse survival than patients with integration-negative tumors and similar survival as patients with HPV-negative HNSCCs [80].…”
Section: Hpv Integration In Relation To Prognosismentioning
confidence: 87%